Ecological aspects of three strains of entomopathogenic nematodes from the department of Lambayeque-Peru - Rodas Adrianzén, Jennifher Elizabeth (2024)
Background Entomopathogenic nematodes (EPN) are used as a biological control agent for diferent insect pests in agriculture. The genera Heterorhabditis and Steinernema are the most used commercially. For an EPN species to be used as a biological controller, it is necessary to know its ecological aspects, including reproductive potential, movement capacity, and mean lethal concentration (LC50). These aspects were evaluated in three EPN strains isolated in Galleria mellonella larvae collected in the Lambayeque-Peru region, to determine if they are promising as biological controllers. The strains of EPN studied are Heterorhabditis sp. (PC9 strain), H. bacteriophora Poinar (PM10 strain), and Steinernema diaprepesi Nguyen y Duncan (SV19 strain). Results Heterorhabditis sp. (PC9 strain) and H. bacteriophora (PM10 strain) had high production of infective juveniles (IJs): 217.750 and 186.800, respectively, while S. diaprepesi (SV19 strain) only reached 84.150 IJs. The movement capacity of Heterorhabditis sp. (PC9 strain) and H. bacteriophora (PM10 strain) reached a depth of 15 cm to parasitize G. mellonella larvae, while S. diaprepesi (SV19 strain) only reached 10 cm. In decreasing order, the LC50 value of S. diaprepesi (SV19 strain), Heterorhabditis sp. (PC9 strain) and H. bacteriophora (PM10 strain) were: 24.03, 13.74, and 8.19 IJs/ml, respectively. Conclusions Heterorhabditis sp. PC9 and H. bacteriophora PM10 are promising a biological control agent because they present great production of IJs, great displacement capacity, and high pathogenicity against G. mellonella. Additionally, both strains present a mixed search strategy or seeker-hunter (seeker-browser).